2015
DOI: 10.1016/j.clim.2015.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Micro and nanoparticle drug delivery systems for preventing allotransplant rejection

Abstract: Despite decades of advances in transplant immunology, tissue damage caused by acute allograft rejection remains the primary cause of morbidity and mortality in the transplant recipient. Moreover, the long-term sequelae of lifelong immunosuppression leaves patients at risk for developing a host of other deleterious conditions. Controlled drug delivery using micro- and nanoparticles (MNPs) is an effective way to deliver higher local doses of a given drug to specific tissues and cells while mitigating systemic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 110 publications
(128 reference statements)
0
43
0
Order By: Relevance
“…Several studies were related to the design of various types of nanostructured scaffolds that could allow the regeneration of different type of tissues [27,28,29]. In addition, it was reported that these materials and matrices have been compared and evaluated for their better biocompatibility and efficacy in supporting the damaged tissue [30,31,32]. …”
Section: Discussionmentioning
confidence: 99%
“…Several studies were related to the design of various types of nanostructured scaffolds that could allow the regeneration of different type of tissues [27,28,29]. In addition, it was reported that these materials and matrices have been compared and evaluated for their better biocompatibility and efficacy in supporting the damaged tissue [30,31,32]. …”
Section: Discussionmentioning
confidence: 99%
“…Along with pre-treatment strategies, delivery mechanisms intended to allow for organ level immunosuppression while leaving the patient's global immune system intact may represent the future of organ specific immunosuppression. These disruptive technologies include micro and nanoparticles carrying immunosuppressants and chemotherapeutics, for example, delivered both systemically and directly to an organ allograft 25,26,28…”
Section: Discussionmentioning
confidence: 99%
“…[130133] CsA inhibits calcineurin, (a serine/threonine phosphatase), decreasing the expression of specific genes that are involved in T-cell activation and the production of interleukins (IL-2), which acts as a lymphocyte mitogen. [134] A recent clinical trial evaluated the use of topical CsA ophthalmic emulsion 0.05%, for the treatment of DED (Restasis©; Allergan Inc, Irvine, California).…”
Section: Ocular Diseasesmentioning
confidence: 99%
“…[11,109,130] Rapamycin inhibits a downstream target known as mTOR (mammalian target of rapamycin) that is needed for upregulation of IL-2 production, which sustains T cell activation and proliferation. [130] The mTOR pathway has also been linked to effects on cellular aging; therefore, mTOR inhibitors, such as rapamycin, prevent the conversion of quiescence to senescence, which has revealed to slow down aging in mice. [168] Slowing down the aging process with rapamycin may also be relevant to the progression of age-related diseases such as AMD.…”
Section: Ocular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation